EXPLORING THE EFFECTIVENESS OF Pseudomonas aeruginosa ISOLATES FOR BIOREMEDIATION OF CRUDE OIL-CONTAMINATED SOILS USING SOYBEAN HULL AS A BIOSTIMULANT: A FOCUS ON ETPH AND PAHs - Ajao, Abdullahi; Jimoh-Hamza, Oluwabukola Kudirat (FUDMA JOURNAL OF SCIENCES, 2024)
The Speciated EPA-16 Polyaromatic Hydrocarbons (PAHs) in crude oil pose significant environmental and health risks due to their harmful properties. This study focused on indigenous bacteria capable of degrading Extractable Total Petroleum Hydrocarbons (ETPHs) and PAHs through a Nutrient-Amended Bioaugmentation Strategy (N-ABS). Crude oil-degrading bacteria were isolated from contaminated soil in Alakiri Community, Rivers State, Nigeria, leading to the identification of four Pseudomonas aeruginosa isolates (KUD1-4) via 16S rRNA gene sequencing. Bioremediation treatments, using both bacterial isolates and Soybean hull as a biostimulant, showed that P. aeruginosa KUD2 achieved the highest removal efficiencies of 96.59% for ETPHs and 80.00% for PAHs. This study underscores the potential of P. aeruginosa KUD2 and Soybean hull in remediating crude oil-contaminated soils.
Keywords: Bioremediation; Indigenous bacteria; Crude oil degradation; Soil pollution; Biosurfactant production